Exergaming Can Be a Health-Related Aerobic Physical Activity - Polechoński, Jacek (Biomed Res Int, 2019)
The purpose of the study was to assess the intensity of aerobic physical activity during exergame training sessions with a moderate (MLD) and high (HLD) level of difficulty of the interactive program “Your Shape Fitness Evolved 2012” for Xbox 360 Kinect in the context of health benefits. The study involved 30 healthy and physically fit students. During the game, the HR of the participants was monitored using the Polar M400 heart rate monitor. The average percentage of maximum heart rate (%HRmax) and heart rate reserve (%HRR) during the game was calculated and referred to the criterion of intensity of aerobic physical activity of American College of Sports Medicine and World Health Organization health recommendations. During the MLD training, the participants achieved on average 69.6 ± 8.7%  HR(max) and 57.0 ± 11.9% HRR (moderate intensity), while performing HLD exercises, they achieved 78.9 ± 8.1%  HR(max) and 70.2 ± 11.3% HRR (vigorous intensity). The time spent in recommended moderate-to-vigorous intensity during 15-min exergame session was 14.6 min (97,1%) for MLD and 14.8 min (99%) for HLD. The intensity of aerobic PA during exergame “Your Shape Fitness Evolved 2012” both medium and high level of difficulty almost all the training sessions was at the level recommended for health benefits. Active video games, especially exergames, containing an element of physical activity, can be used to increase the weekly dose of PA in the direction recommended for health benefits.